1999
DOI: 10.1002/(sici)1521-3773(19990903)38:17<2554::aid-anie2554>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

C6F5XeCl and [(C6F5Xe)2Cl][AsF6]: The First Isolated and Unambiguously Characterized Xenon(II) Chlorine Compounds

Abstract: Xenon(II) chlorine compounds can be obtained as the isolable organo derivatives C(6)F(5)XeCl and [(C(6)F(5)Xe)(2)Cl][AsF(6)] (whose cation is depicted) in 85 and 91 % yield, respectively. These compounds decompose vigorously at 36 degrees C and 100 degrees C, respectively, leading to the formation of C(6)F(5)Cl and Xe gas and of C(6)F(5)Cl, C(6)F(6), and [C(6)F(5)Xe][AsF(6)], respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0
3

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 6 publications
0
18
0
3
Order By: Relevance
“…XeCl 2 , however, has only been detected in matrix, [1] not counting the single unreproduced report, in which it was claimed XeCl 2 could be prepared by high frequency discharge of Xe, F 2 , and SiCl 4 or CCl 4 and that it is stable up to 80 8C. [2] Cocrystallisates of RbCl or CsCl and, XeO 3 are known, however, which have Xe ± Cl contact distances of 275(5) to 297(1) pm.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…XeCl 2 , however, has only been detected in matrix, [1] not counting the single unreproduced report, in which it was claimed XeCl 2 could be prepared by high frequency discharge of Xe, F 2 , and SiCl 4 or CCl 4 and that it is stable up to 80 8C. [2] Cocrystallisates of RbCl or CsCl and, XeO 3 are known, however, which have Xe ± Cl contact distances of 275(5) to 297(1) pm.…”
mentioning
confidence: 99%
“…Because of its instability in solution no further detailed structure information is available, but it can be assumed that it contains a real XeÀCl bond. [4] Since the bond strength is stronger in XeF than in XeF 2 , salts with the XeCl ion could be the most stable species with a XeÀCl bond.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…and Xe-Cl bonds [6]. These compounds are remarkable because they involve, by analogy with XeF2, semi-ionic 3-center/4-electron bonds [7][8][9] that are only half as strong as the previously known predominantly covalent Xe-C and Xe-Cl bonds in the [XeCeFs]* [10,11] and [XeCl]^ [6] cations, respectively. Although the synthesis of CFsXeCFs hac^een claimed ^eady) in 1979 [12], all attempts to verify this claim have failed so far [5].…”
Section: Karl O Christe"mentioning
confidence: 97%
“…In a different approach, the group of Professor Naumann at the University of Koeln, Germany, found that CeFsXeCeFs and CeFsXeF are directly accessible from XeFa and (CH3)3SiC6F5 [5]. and Xe-Cl bonds [6]. These compounds are remarkable because they involve, by analogy with XeF2, semi-ionic 3-center/4-electron bonds [7][8][9] that are only half as strong as the previously known predominantly covalent Xe-C and Xe-Cl bonds in the [XeCeFs]* [10,11] and [XeCl]^ [6] cations, respectively.…”
Section: Karl O Christe"mentioning
confidence: 99%